Everolimus-based, calcineurin-inhibitor-free regimen in recipients of de-novo kidney transplants: an open-label, randomised, controlled trial - Budde, Klemens; Becker, Thomas; Arns, Wolfgang; Sommerer, Claudia; Reinke, Petra; Eisenberger, Ute; Kramer, Stefan; Fischer, Wolfgang; Gschaidmeier, Harald; Pietruck, Frank (The lancet, 2011)
Background - Non-nephrotoxic immunosuppressive strategies that allow reduction of calcineurin-inhibitor exposure without compromising safety or efficacy remain a goal in kidney transplantation. Immunosuppression based on the mammalian-target-of-rapamycin inhibitor everolimus was assessed as a strategy for elimination of calcineurin-inhibitor exposure and optimisation of renal-graft function while maintaining efficacy. - Methods - In the ZEUS multicentre, open-label study, 503 patients (aged 18-65 years) who had received de-novo kidney transplants were enrolled. After initial treatment with ciclosporin, based on trough concentrations, and enteric-coated mycophenolate sodium (1440 mg/day, orally), corticosteroids (≥5 mg/day prednisolone or equivalent, orally), and basiliximab induction (20 mg, intravenously, on day 0 [2 h before transplantation], and on day 4), 300 (60%) patients were randomly assigned at 4·5 months in a 1:1 ratio to undergo calcineurin-inhibitor elimination (everolimus-based regimen that was based on trough concentrations [6-10 ng/mL] and enteric-coated mycophenolate sodium [1440 mg/day] with corticosteroids), or continue standard ciclosporin-based treatment. Randomisation was done by use of a central, validated system that automated the random assignment of treatment groups to randomisation numbers. The primary objective was to show better renal function (glomerular filtration rate [GFR]; Nankivell formula) with the calcineurin-inhibitor-free everolimus regimen at 12 months after transplantation. Analysis was by intention to treat. This study is registered with ClinicalTrials.gov, number NCT00154310. - Findings - 118 (76%) of 155 everolimus-treated patients and 117 (81%) of 145 ciclosporin-treated patients completed treatment with study drug up to 12 months after transplantation. At this timepoint, the everolimus regimen was associated with a significant improvement in GFR versus the ciclosporin regimen (71·8 mL/min per 1·73 m2 vs 61·9 mL/min per 1·73 m2, respectively; mean difference 9·8 mL/min per 1·73 m2, 95% CI −12·2 to −7·5). Rates of biopsy-proven acute rejection were higher in the everolimus group than in the ciclosporin group after randomisation (15 [10%] of 154 vs five [3%] of 146; p=0·036), but similar for the full study period (23 [15%] vs 22 [15%]). Compared with the ciclosporin regimen, higher mean lipid concentrations, slightly increased urinary protein excretion, and lower haemoglobin concentrations were noted with the everolimus regimen; thrombocytopenia, aphthous stomatitis, and diarrhoea also occurred more often in the everolimus group. A higher incidence of hyperuricaemia was noted with ciclosporin. - Interpretation - Early elimination of calcineurin inhibitor by use of everolimus-based immunosuppression improved renal function at 12 months while maintaining efficacy and safety, indicating that this strategy may facilitate improved long-term outcomes in selected patients. - Funding - Novartis Pharma.
Gesehen am 24.06.2022